KAJIAN STATISTIK SEISMISITAS KAWASAN SUMATERA - Warni Asnita; Didik Sugiyanto; Ibnu Rusydy (Jurnal Natural, 2016)
The research was conducted in order to identify the distribution of seismicity, repeated periods of earthquakes and the probability of earthquake in Sumatra using Likelihood Maximum methods. Earthquake data from the ISC and USGS catalogue were used. Earthquake data from 1914-2014 (100 year span)  with magnitude of (M)≥5 SR and depth (h)≤100 km that is located at 60LS – 100LU and 920BT – 1080BT. The latitude and longitude coordinates were divided into 21 regions. The results showed distribution of seismicity in Sumatran as much as 3634 events of earthquake during the 100 last years. The distribution of seismicity in Sumatra is quite high. From data shown, there was value a, which is between 4.81 - 9.94 and value b which is between 0.54 - 1.32.  This condition indicated an index value of M≥5 SR, which is between 0.006 - 0.076 and repeated periods between 13 - 175 years with the probability of earthquake M≥5 SR between 5.6% - 99.9% for T (time) = 10, 50 and 100 years.